Characterization of Four Novel Bacteriophages Isolated from British Columbia for Control of Non-typhoidal Salmonella in Vitro and on Sprouting Alfalfa Seeds - Fong, Karen; LaBossiere, Brett; Switt, Andrea I. M.; Delaquis, Pascal; Goodridge, Lawrence; Levesque, Roger C.; Danyluk, Michelle D.; Wang, Siyun (Frontiers in Microbiology, 2017)
Alfalfa sprouts have been linked to numerous North American outbreaks of Salmonella in recent years. Conventionally, treatments involving chlorine, heat, and irradiation are used for alfalfa seed sanitation. However, such treatments may be highly variable in their efficacy for pathogen control and/or detrimental to sprout quality, therefore negatively perceived by consumers advocating for natural alternatives. The usage of bacteriophages for pathogen control in sprouts has been previously explored, although with conflicting and inconsistent results. Lytic phages, viral predators of bacteria, represent an attractive approach as they provide several advantages compared to conventional treatments, such as their high specificity for bacterial targets and their ubiquity in nature. In this study, four Salmonella phages were isolated from British Columbia, Canada and characterized with respect to host range, burst size, latent period, and environmental stability to assess their potential to control Salmonella. Phage isolate SI1 showed the greatest host range, highest burst size and shortest latent period, greatest stability across all pH and temperatures and was the most effective in control of S. Enteritidis in vitro. Therefore, SI1 was chosen for treatment of sprouting alfalfa seeds artificially contaminated with S. Enteritidis with a multiplicity of infection (MOI) of ~110 PFU/CFU. A significant (p<0.05) reduction of 38.3  3.0 % of viable Salmonella cells was observed following two h of phage treatment. On days two to six of the sprouting process, reductions of Salmonella were also observed, but were not significant compared to the control (p>0.05). It was further demonstrated that the sprout yield was not significantly (p>0.05) affected by phage treatment. These results highlight the potential of phages recovered from the British Columbia environment for use as biocontrol agents against Salmonella, although differing efficacies in vitro was observed. Moreover, the effectiveness of SI1 to significantly (p<0.05) control Salmonella on sprouting alfalfa seeds on day one of treatment was demonstrated. Although promising, future work should aim to optimize this treatment to achieve more effective, and longer lasting, biocontrol of Salmonella in sprouting alfalfa seeds.